PENERAPAN MEDIA VISUAL TEXT CARD MATERI SIFAT MUSTAHIL ALLAH PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) DI KELAS III SDIT AL-MAWADDAH WARRAHMAH KOLAKA - M Irfan; Ikhwana Ikhwana; Rismawati Rismawati; Hamsidar Hamsidar; Kamiliah Rahmah; Suhardin Suhardin; Rina Nur Afifah; Alam Syah (IAI Al-Mawaddah Warrahmah Kolaka, 2018)
The use of visual media is one of several components that underlie the realization of an effective learning. The subjects of the trial were students who were respondents in a study. In this study the subject of the trial was the students of class III SDIT Al-Mawaddah Warrahmah Kolaka with a total of 8 students. This research is located at SDIT Al-Mawaddah Warrahmah Kolaka which is located at Pondok Pesantren Street, Lamokato Village, Kec. Kolaka Kab. Kolaka. The conclusion that can be taken after doing this research is the response of students to the Text Card media as a learning medium in terms of learning motivation, 0% in the very poor category, 0% not good, 25% good, and 75% very good. This means students have been motivated to learn using the Text Card media. The application of Text Card media in the subjects of Islamic Religion in class III SDIT Al-Mawarrahmah Kolaka, namely the first student is distributed cards. Second, students are divided into two groups, then they are asked to perfect the writing in the carton. The teacher's response to Text Card media as a learning medium in terms of learning motivation says that this media has a positive impact on students in terms of learning motivation.